2021
DOI: 10.1038/s41598-021-03662-5
|View full text |Cite
|
Sign up to set email alerts
|

circRNA N6-methyladenosine methylation in preeclampsia and the potential role of N6-methyladenosine-modified circPAPPA2 in trophoblast invasion

Abstract: Here, we performed N6-methyladenosine (m6A) RNA sequencing to determine the circRNA m6A methylation changes in the placentas during the pathogenesis of preeclampsia (PE). We verified the expression of the circRNA circPAPPA2 using quantitative reverse transcription-PCR. An invasion assay was carried out to identify the role of circPAPPA2 in the development of PE. Mechanistically, we investigated the cause of the altered m6A modification of circPAPPA2 through overexpression and knockdown cell experiments, RNA im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…Previous studies have shown that m 6 A alterations affect mRNA or miRNA targeting and could be associated with the progression of various diseases 31,32 . Several previous studies support that m 6 A RNA methylation in the placental trophoblast of PE provides a novel posttranscriptional mechanism for aberrant m 6 A modification in PE, which may contribute to preeclamptic trophoblast dysfunction 16,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that m 6 A alterations affect mRNA or miRNA targeting and could be associated with the progression of various diseases 31,32 . Several previous studies support that m 6 A RNA methylation in the placental trophoblast of PE provides a novel posttranscriptional mechanism for aberrant m 6 A modification in PE, which may contribute to preeclamptic trophoblast dysfunction 16,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, PE has been an intractable complication associated with pregnancy and brought about increasing mortality in both pregnant women and fetuses (Mol et al 2016). Previous studies indicated that PE was always accompanied by trophoblast dysfunction due to ER stress, increased ROS production, and apoptosis rate (Capatina et al 2021), and m 6 A modification could play an important role in this dysfunction (Taniguchi et al 2020;Zhang et al 2021b). While aberrant m 6 A modification for trophoblast dysfunction during PE has been observed (Wang et al 2020;Gu et al 2021;Guo et al 2022), there are no reports on the relationship between the ER stress state in trophoblasts and m 6 A modification in PE.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid development makes the prenatal period particularly vulnerable because of the complicated trajectory of cells and environmental perturbations. To maintain placental homeostasis, several epigenetic mechanisms have been highlighted to drive short- and long-term gene expression changes ( Nelissen et al, 2011 ), including DNA methylation ( Koukoura et al, 2012 ; Lorincz and Schubeler, 2017 ), histone modifications ( Meister et al, 2021 ), non-coding RNAs ( Du et al, 2021 ; Zhang et al, 2021 ; Zarkovic et al, 2022 ), and also RNA methylation ( Mu et al, 2022 ). As one of the most prevalent internal modifications in RNAs, N6-methyladenosine (m 6 A) extensively regulate RNA metabolism ( Jia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%